The Effects of Instructional Approaches and Motivation on Students’ Reading Comprehension at MTS’s Amal Shaleh Simalingkar - Sari, Kumala; Arfanti, Yulia; Asnawi (International Journal of Educational Research Excellence (IJERE), 2024)
Reading comprehension is a fundamental skill that serves as the foundation for effective learning and intellectual growth. GSSR's comprehensive approach extends beyond the classroom, fostering a lifelong appreciation for reading. A significant area of focus in educational psychology is the relationship between motivation and reading comprehension. This relationship has been shown to influence student engagement, perseverance, and, ultimately, academic achievement. The objective of this study was to ascertain whether the GSSR approach is more effective than the non-GSR treatment. Additionally, the study aimed to determine whether students with high levels of motivation demonstrate superior reading comprehension skills compared to those who are less motivated. Finally, the study sought to investigate whether there is a relationship between teaching the GSSR approach versus the conventional approach and the level of motivation on students' reading comprehension. This study employed a quantitative research design. The study was conducted at MTS Amal Saleh. The study sample consisted of 62 students from grades 8A, 8B, and 8C. The data analysis employed descriptive analysis, the Wilcoxon test, and the N-gain Score test. The findings indicated that the GSSR approach was more effective than the conventional method in enhancing students' reading comprehension. The success rate for the former was 55%, while the latter was 81.81%. Additionally, the students' mean scores were 70.25 and 77.75, respectively, for classes 8B and 8C. The enhancement of students' reading comprehension with high motivation yields superior outcomes compared to the improvement of students' reading comprehension with low motivation. This was demonstrated by the fact that the GSSR + Motivation method resulted in a 76.81% increase in the pass rate and a 38.44-point increase in the average score.